Disentangling Stigma from Functional Neurological Disorders: Conference Report and Roadmap for the Future - Rommelfanger, Karen S.; Factor, Stewart A.; LaRoche, Suzette; Rosen, Phyllis; Young, Raymond; Rapaport, Mark H. (Frontiers in Neurology, 2017)
On October 9 and 10, 2015, a conference entitled “Controversial labels and clinical uncertainties: psychogenic disorders, conversion disorder, and functional symptoms” was held at the Center for Ethics, Emory University, Atlanta, GA. This conference brought together a select group of 30 distinguished thought leaders and practitioners– including ethicists, researchers, clinicians, humanities scholars, and advocates to discuss the unique challenges and controversies related to the diagnosis, treatment, and stigma for patients with what is currently recognized as functional (“psychogenic”) neurological disorders. Our group of experts explored the conflicts and ethical tensions within healthcare that must be addressed in order to advance care for these disorders. What follows is a reflection on the conversations between conference attendees outlining key challenges and value conflicts in the diagnosis and treatment of patients with functional disorders. With this report we aim to provide a roadmap for reducing stigma and improving care for functional neurological disorders. A path forward would involve 1) Setting a multifactorial research agenda that equally prioritized access to effective psychotherapy as well as identification of novel biomarkers; 2) Empowering patients with FND to be heard and to drive changes in care; and 3) Reducing isolation for clinicians by providing formal training and setting up multidisciplinary care teams, and support networks.